Low Molecular Metabolites Of Fungi. Dimetoxystachibotrin From Stacybotrys Chartarum - Farhod Qalandarov (Genius Journals, 2025)
As a result of studies carried out in our country, information was obtained on the distribution of fungi of the genus Stachybotrys, their morphology, ultrastructure, cytology, biotechnology of cultivation on cellulose-containing nutrient media, ensiling of such solid plant waste as guzapoya, rice straw, corn stalks. Stachybotrys chartarum produces a number of low molecular weight compounds. A technique has been developed for the isolation and separation of the sum of extractive substances - waste products of the fungus Stachybotrys chartarum grown under laboratory conditions on various nutrient media
Keywords: Stachybotrys chartarum; chromatography; spectrum